Environmental exposure to organophosphate esters and suspected non-alcoholic fatty liver disease among US adults: A mixture analysis - Chai, Haisheng; Hu, Weiye; Dai, Yaoyao; Zhu, Xiaohan; Qian, Ping'an; Zhu, Junfeng (Frontiers in Public Health, 2022)
Objectives: Nonalcoholic fatty liver disease (NAFLD) is the most common chronic liver disease worldwide. We determined whether urine organophosphate ester (OPE) levels and the occurrence of NAFLD in individuals in the United States are correlated. Methods: The current study included 1102 people aged 20 years with information on urine OPE metabolites, NAFLD, and underlying variables from the U.S. National Health and Nutrition Examination Survey 2011–2014. NAFLD is suspected when the ultrasonographic fatty liver indicator is 30 and no remarkable alcohol consumption or other probable causes of chronic liver disease are present. Individual OPE metabolites and OPE combinations were linked to NAFLD using logistic regression and weighted quantile sum (WQS) regression. All analyses were carried out separately on males and females. The possible impacts of age, serum total testosterone (TT), and menopausal state, as well as the importance of the interaction term with exposure, were investigated using stratified analysis. Results: Bis(2-chloroethyl) phosphate and bis(1,3-dichloro-2-propyl) phosphate were associated with NAFLD in all males after adjusting for covariates (P<0.05). A combination of OPEs (OPE index) was positively linked with NAFLD in the WQS analysis of all males (odds ratio for OPE index: 1.52; 95% CI: 1.06, 2.19). Stratified analyses for males revealed that considerable connections were largely confined to individuals over 60 years old or with low total testosterone. In women with NAFLD, the connection was limited and inconsistent, except for the OPE index, which was positively linked with NAFLD in postmenopausal women.